Cardiopulmonary response to exercise and heart failure with preserved ejection fraction risk: a comparative analysis of HFA-PEFF and H2FPEF scores. (3rd October 2022) - Lazzeroni, D; Marchini, C; Centorbi, C S; Moderato, L; Brambilla, L; Bini, M; Guazzi, E; Magnani, G; Aschieri, D; Piepoli, M; Nicolini, F; Coruzzi, P
Abstract: Background: Exercise intolerance evaluation in Heart failure with preserved ejection fraction (HFpEF) remains challenging, since several mechanisms (diastolic and systolic reserve abnormalities, low chronotropic reserve (CR), ventricular or vascular stiffening, atrial dysfunction, pulmonary hypertension, endothelial dysfunction, energetic abnormalities and autonomic dysfunction) play different roles. European Society of Cardiology HF guidelines recently suggested a stepwise non-invasive HFpEF diagnostic approach consisting of three steps: clinical, echocardiographic and laboratory data (natriuretic peptides), named HFA-PEEF Score, and finally, in case of inconclusive findings, diastolic stress echocardiography data. Cardiopulmonary exercise testing (CPET) may represent a promising further non-invasive diagnostic tool in HFpEF evaluation since allow to assess the presence of reduced functional capacity as well as to differentiate between cardiovascular, ventilatory or peripheral causes. Purpose: Whether increased risk of HFpEF is associated with different and specific cardiopulmonary responses to exercise is still an open issue and this was the aim of our study. Methods: 1.156 consecutive subjects with preserved ejection fraction undergoing cardiovascular evaluation at the Cardiovascular Prevention Center of Fondazione Don Gnocchi & University of Parma were enrolled. All subjects underwent cardiovascular evaluation and echocardiography, HFA-PEEF and H2FPEF Score assessment and cardiopulmonary exercise testing. Different cardiopulmonary response to exercise were compared between different groups of HFpEF risk. Results: According to HFA-PEEF Score, 675 (58%) had 0 or 1 point, 253 (22%) had 2 points and 230 (20%) had 3 or 4 points (moderate-to-high risk). Patients with both higher HFA-PEEF and H2FPEF Score showed lower functional capacity, expressed as low peak V02 (p<0.001) associated with lower oxygen pulse (V02/HR) (p<0.001), cardiac output (CO) at peak (p<0.001), CR (p<0.001), ventilatory efficiency (expressed as VE/VC02 slope) (p<0.001) and oxygen uptake extraction (OUES) (p<0.001). Moreover, higher H2FPEF Score patients showed lower stroke volume (SV) at peak (p<0.001), while high HFA-PEEF score was not associated to SV at peak (Table 1 and Figure 1). More specifically, the presence of reduced cardiovascular efficiency (V02/Watt Slope <7) was associated to a 2.2-fold higher risk of HFpEF (p=0.003), impaired ventilator efficiency (VE/VCO2 Slope >35) to a 2.4-fold higher risk (p<0.001), reduced CR (<70%) 4.3-fold higher risk (p<0.001). Conclusions: Different degrees HFpEF risk, estimated using both HFA-PEEF and H2FPEF score, are associated with different cardiopulmonary responses to exercise. High HFpEF risk patients show low functional capacity, cardiovascular and ventilator efficiency due to lower cardiac output at peak, despite preserved ejection fraction, associated to lower chronotropic response to exercise. Funding Acknowledgement: Type of funding sources: None.